Effect of dietary substitution of corn with Flammulina velutipes residue on growth performance, serum biochemical indicators, slaughter performance and cecal microbiota in geese - Huiying Wang; Guangquan Li; Xianze Wang; Yi Liu; Yunzhou Yang; Cui Wang; Shaoming Gong; Daqian He (Italian Journal of Animal Science)
The experiment sought to determine the effects of substituting Flammulina velutipes residue (FVR) for corn on growth performance, serum biochemical parameters, slaughter performance and caecum microbiota of geese. One hundred and ninety-two 35old Hordobagy geese were used in this experiment, and they were divided into four groups and fed with various diets for 28 d. The geese in the control group were fed with a basal diet. The other groups substituted 12%, 24% and 32% FVR for corn in their diets, respectively. There was no significant difference in the feed/gain ratio between the addition of 12% and 24% FVR to the diet, however, these additions considerably raised final body weight, average daily feed intake, and average daily growth (p < 0.05). When 24% FVR was substituted for corn in the diet, the levels of albumin (ALB) and high-density lipoprotein cholesterol (HDL-C) dramatically rose (p < 0.05). The examination of caecal microbiota revealed that the substitution of FVR for corn greatly increased both the variety and quantity of the caecal microbiota as well as the amount of bacteria that produce short-chain fatty acids (SCFAs). In conclusion, FVR has the potential to be an effective corn replacement with a 24% acceptable substitution level.